2018
DOI: 10.1371/journal.pone.0194115
|View full text |Cite
|
Sign up to set email alerts
|

Generational changes in multiple sclerosis phenotype in North African immigrants in France: A population-based observational study

Abstract: BackgroundThe incidence of multiple sclerosis (MS) changes from generation to generation in ethnically different immigrants compared with native-born people. We aimed to determine whether there are generational changes in MS phenotypes among North African immigrants in France.MethodsCohort study with data from a population-based MS registry to compare the clinical characteristics of 80 first (NAG1) and 167 second (NAG2) generation North Africans with MS living in France with 5200 native-born Europeans. Adjuste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Despite these limitations, this same issue of racial groups has also been examined in another demyelinating condition -multiple sclerosis. It has been shown that African patients have a worse visual and overall prognosis and that place of residence seems to be protective, which is in line with our findings for NMOSD (Aurencao et al, 2016;Merle et al, 2005;Naismith et al, 2006;Nardin et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Despite these limitations, this same issue of racial groups has also been examined in another demyelinating condition -multiple sclerosis. It has been shown that African patients have a worse visual and overall prognosis and that place of residence seems to be protective, which is in line with our findings for NMOSD (Aurencao et al, 2016;Merle et al, 2005;Naismith et al, 2006;Nardin et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Other studies have demonstrated higher disability accumulation rates in MENA-MS patients versus EUR-MS patients residing in France, 13,14 with a generational effect on disease severity. 15 The generational effect was also observed in our study, but it is important to note that our study was not powered to assess such an effect making it difficult to draw definitive conclusions. It is unclear to what extent the immigration process, other socioeconomic determinants, and the different environmental exposures change disease phenotype in this population, and further study is warranted.…”
Section: Discussionmentioning
confidence: 58%
“…13,14 Furthermore, first-generation MS patients of MENA descent (MENA-MS) immigrants have a more aggressive disease course than second-generation MENA-MS patients, suggesting a generational effect on MS phenotype. 15 Generally, there is a dearth of information detailing the clinical course of immigrating MENA-MS patients and the published data remain inconclusive. 9,13,16 Canada has a large proportion of immigrants from diverse countries, with a relatively large population of immigrants originating from MENA countries, making it an ideal location to study the intersection of genetics, environment, and their effect on disease phenotype in specific populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immigrants may encounter unique barriers in accessing mental healthcare due to language difficulties, lack of health system literacy, and stigma toward mental health problems in their communities 27 , 28 Third, clinicians should follow these patients closely and consider early intervention as mental health conditions have been associated with greater long-term disability in MS, and immigrants and non-White persons may already be at risk for earlier disability accumulation. 31 33 In a large population-based cohort study of incident MS cases in Canada, psychiatric comorbidity was associated with subsequent greater accrual of neurologic disability as measured by the Expanded Disability Status Scale (EDSS). 26 Another large cohort study in Sweden found that persons having MS with depression had a higher risk of reaching major disability milestones, including EDSS scores of 3.0, 4.0, and 6.0.…”
Section: Discussionmentioning
confidence: 99%